The Mechanism of Lending Poor Loans and its relation to Social Goals - Muhammad, Osamah; Arees, Zeinab (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Many banks and finance institutes spread around the world, which provides its bank services, but most of these services didn’t reach to the poor, whom needs financial support to improve their living standard, by having a chance that loans can provide to the poor and by running their own business maybe will provide high earnings in the future and relieve them of poverty. This study aims to know the mechanism of lending poor loans, which providing by microfinance institutes, Islamic microfinance institutes and banks to the poor, in addition to this we’ll study the connection of their work mechanism with social goals, that attempt in the first place to reduce poverty in the society.